Measuring the Success of SDGs Implementation Bonjeruk Village, Jonggat Sub-district, Central Lombok District, West Nusa Tenggara - Izana, Nyimas Nadya; Susanti, Anik (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2025)
ABSTRACT Sustainable development has become a key strategy in addressing the challenges of economic inequality and environmental degradation at the village level. This study aims to assess the success of implementing the Village Sustainable Development Goals (SDGs) in Bonjeruk Village, Jonggat Sub-district, Central Lombok Regency, by focusing on community participation based on Cohen and Uphoff’s theory, which includes the dimensions of planning, implementation, utilization, and evaluation. A descriptive quantitative approach was applied by distributing closed-ended questionnaires using a Likert scale to 21 respondents selected through simple random sampling, supported by observations and interviews to strengthen the analysis. The results indicate that community participation is relatively high, particularly in the utilization stage of the tourism village program, with an average score of 3.37. This is reflected in the dominance of “agree” responses, where 52.4% of respondents acknowledged that village tourism activities contribute to economic welfare, 57.1% strongly agreed that information on tourism development programs is well communicated, and 52.4% confirmed the support of the village government through resource provision. The active involvement of the community in strategic planning, program implementation, economic benefit distribution, and program evaluation illustrates a collaborative success between the village government, the Tourism Awareness Group (Pokdarwis), and local communities. The findings suggest that structured and sustainable community participation through institutions, mechanisms, and clear regulations is the key to the successful implementation of the Village SDGs in Bonjeruk, positioning the village as a model for sustainable and collaborative tourism village development.Keywords: Village SDGs, community participation, Pokdarwis, tourism village ABSTRAK Pembangunan berkelanjutan telah menjadi strategi utama dalam mengatasi tantangan ketimpangan ekonomi dan degradasi lingkungan di tingkat desa. Penelitian ini bertujuan untuk menilai keberhasilan implementasi Tujuan Pembangunan Berkelanjutan Desa (SDGs) di Desa Bonjeruk, Kecamatan Jonggat, Kabupaten Lombok Tengah, dengan berfokus pada partisipasi masyarakat berdasarkan teori Cohen dan Uphoff, yang meliputi dimensi perencanaan, pelaksanaan, pemanfaatan, dan evaluasi. Pendekatan kuantitatif deskriptif diterapkan dengan mendistribusikan kuesioner tertutup menggunakan skala Likert kepada 21 responden yang dipilih melalui simple random sampling, didukung oleh observasi dan wawancara untuk memperkuat analisis. Hasil penelitian menunjukkan bahwa partisipasi masyarakat relatif tinggi, khususnya pada tahap pemanfaatan program desa wisata, dengan skor rata-rata 3,37. Hal ini tercermin dari dominasi respons